NOWE WYZWANIA W SFERZE PRAWODAWSTWA MIEJSCOWEGO NA PRZYKŁADZIE GMINY - Szyrski, Mariusz (Zeszyty Prawnicze, 2017)
New Challenges Concerning Local Law Summary This article presents a number of challenges currently faced by local government law. In the first part of the article, the author focuses on thoroughly analyzing institutions of local law, based on doctrine and jurisprudence. The rest of the article presents the current problems related to the functioning of local governments in the light of legislation. The text presents, inter alia, issues connected with the development of the private sector and the NGO sector. Furthermore, it describes the basic problems related to the statutes constituted in community including the division between regulatory and commissioned tasks in the community. Finally, the author presents conclusions de lege ferenda which are primarily associated with the need to review the catalogue of community’ commissioned and regulatory tasks related to the cooperation with social partners, and the need to broaden the catalogue of the Local Government Act, so that all the objectives of the community can be found in the same political act.